PENGARUH RISIKO BISNIS, PERTUMBUHAN PENJUALAN DAN SET KESEMPATAN INVESTASI TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hikalmi Hikalmi; Ahmad Fadhillah (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2019)
This study aims to examine how much "Effect of Business Risk, Sales Growth and Investment Opportunity Set on Capital Structure in Manufacturing Companies Listed on the Indonesia Stock Exchange". In this study the samples taken are manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2018. The data analysis method used in this study was using multiple regression analysis. The results of the research partially show that business risk influences the capital structure, sales growth influences the capital structure and investment opportunity sets influence the capital structure. The results of the study simultaneously show that business risk, sales growth and investment opportunity sets affect the capital structure of manufacturing companies listed on the Indonesia Stock Exchange. It is hoped that this research can be used as a work in increasing knowledge that can further broaden the mindset of the readers, especially regarding the effect of the influence of Business Risk, Sales Growth and Investment Opportunity Set on Capital Structure in Manufacturing Companies Listed on the Indonesia Stock Exchange.